Wideacre - Gregory, Philippa, ....- (London : HarperCollinsPublishers, 2002)
Wideacre Hall, set in the heart of the English countryside, is the ancestral home that Beatrice Lacey loves. But as a woman of the eighteenth century she has no right of inheritance. Corrupted by a world that mistreats women, she sets out to corrupt others. Sexual and wilful, she believes that the only way to achieve control over Wideacre is through a series of horrible crimes, and no-one escapes the consequences of her need to possess the land.
Keywords: Fiction